Compliance effects of sovereign debt cuts - Eckhard Janeba; Armin Steinbach (Center for Economic Studies and ifo Institute (CESifo), 2019)
The controversy about sovereign debt cuts loomed prominently throughout crisis in the European Union (EU), as the EU legal rules were viewed to impose strict limitations on debt restructuring involving public creditors due to moral hazard concerns enshrined in the legal ban on bailouts. This analysis explores the economic plausibility of the legal regime, with the applicable legal standard capturing the impact of debt restructuring on the debtor's expected compliance with fiscal rules. Our theory shows that the effect of debt cuts on fiscal compliance depends on two effects, the direction of which determines the overall effect on expected fiscal compliance. We empirically review the plausibility of our theoretical results by exploiting survey data from members of state parliaments in Germany. Data limitations notwithstanding, our results offer some plausibility that haircuts can make fiscal compliance more attractive and likely. The results call for re-visiting the legal framework applicable to debt cuts EU rules.
Keywords: H00; 330; debt restructering; fiscal rules; compliance; German debt brake